Osteoarthritis: Patient Expectations about Future Pain, Stiffness and Function. (3rd December 2014) - Dwek, Marie‐Rose; McBain, Hayley; Cleanthous, Sophie; Shipley, Michael; Newman, Stanton
Abstract Objectives The aim of the present study was to examine the difference between osteoarthritis patients' self‐reported assessments of current pain, stiffness and physical function and their expectations of these symptoms in one and five years' time, and to determine the significant predictors of positive expectations. Methods Eighty patients completed ratings of baseline assessments and one‐ and five‐year expectations of pain, stiffness and physical function using the Western Ontario and McMaster Osteoarthritis Index (WOMAC). Measures of illness perceptions, coping styles, health values, satisfaction, quality of life, optimism, self‐esteem and moods were also collected at baseline. Agreement between patients' current assessment and expectations were calculated using intra‐class correlations (ICCs). Paired‐sample t‐tests were conducted to look at differences between assessments. Univariate logistic regressions were then performed to identify the variables significantly associated with positive expectations of pain, stiffness and function. Significant variables (p < 0.05) were entered into a forward stepwise multivariate logistic regression to identify unique independent predictors of positive expectations for each of the WOMAC subscales. Results Differences were found between current assessments and expectations, with the majority of patients being positive about future symptoms. There were some differences between the predictors for one‐ and five‐year expectations, with current assessments of health status only affecting five‐year expectations. Conclusions It is necessary to investigate further the variables that may contribute to positive expectations in osteoarthritis patients in order to manage the condition more effectively. Copyright © 2014 John Wiley & Sons, Ltd.